2000
DOI: 10.1021/tx990155o
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Involvement of N-Methylthiourea, a Ring Cleavage Metabolite, in the Hepatotoxicity of Methimazole in Glutathione-Depleted Mice:  Structure−Toxicity and Metabolic Studies

Abstract: In mice depleted of GSH by treatment with buthionine sulfoximine (BSO), methimazole (2-mercapto-1-methylimidazole, MMI) causes liver injury characterized by centrilobular necrosis of hepatocytes and an increase in serum alanine transaminase (SALT) activity. MMI requires metabolic activation by both P450 monooxygenase and flavin-containing monooxygenase (FMO) before it produces the hepatotoxicity. MMI and its analogues were examined for the ability to increase SALT activity in GSH-depleted mice. Saturation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 24 publications
2
57
0
Order By: Relevance
“…For instance, the cases of clinical hepatotoxicity and/or nephrotoxicity that were noted with the antithyroid drug methimazole (Martinez-Lopez et al, 1962) and the antiparasitic agent thiabendazole (Manivel et al, 1987) have been causally linked with their metabolism to the proximal toxicants N-methylthiourea and thioformamide, respectively, via an initial P450-catalyzed oxidative ring scission of the 2-mercaptobenzimidazole and thiazole motifs present in these drugs. S-oxidation of the N-methylthiourea and thioformamide metabolites to reactive metabolites by FMO enzymes is believed to represent the key step resulting in toxicity (Mizutani et al, 1993(Mizutani et al, , 2000. Consistent with our design philosophy, the N1-substituted-6-aryl-2-thiouracil class of MPO inhibitors (represented in our present study by compound 1) were stable toward metabolism in NADPH-supplemented human liver microsomes and/or cryopreserved human hepatocytes (Ruggeri et al, 2015), and they were latent to the formation of reactive species, as judged from the absence of GSH conjugates in human recombinant MPO and human liver microsomes supplemented with an excess of the thiol nucleophile.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the cases of clinical hepatotoxicity and/or nephrotoxicity that were noted with the antithyroid drug methimazole (Martinez-Lopez et al, 1962) and the antiparasitic agent thiabendazole (Manivel et al, 1987) have been causally linked with their metabolism to the proximal toxicants N-methylthiourea and thioformamide, respectively, via an initial P450-catalyzed oxidative ring scission of the 2-mercaptobenzimidazole and thiazole motifs present in these drugs. S-oxidation of the N-methylthiourea and thioformamide metabolites to reactive metabolites by FMO enzymes is believed to represent the key step resulting in toxicity (Mizutani et al, 1993(Mizutani et al, , 2000. Consistent with our design philosophy, the N1-substituted-6-aryl-2-thiouracil class of MPO inhibitors (represented in our present study by compound 1) were stable toward metabolism in NADPH-supplemented human liver microsomes and/or cryopreserved human hepatocytes (Ruggeri et al, 2015), and they were latent to the formation of reactive species, as judged from the absence of GSH conjugates in human recombinant MPO and human liver microsomes supplemented with an excess of the thiol nucleophile.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that in vivo GSH-depletion can potentiate the olfactory toxicity of some compounds (2,7). In GSH-depleted mice, methimazole exposure will induce a centrilobular hepatic necrosis (23,24). The effects of methimazole on the morphology of the olfactory mucosa in GSH-depleted animals or the effect of methimazole on the level of GSH in the olfactory mucosa have not been reported, however.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, both the olfactory toxicity and the hepatotoxicity of MMZ depend on the in vivo formation of its electrophilic intermediates. It has been proposed that the bioactivation of MMZ is catalyzed sequentially by P450 and FMO, with P450 enzymes catalyzing the epoxidation of the C-4,5 double bond of MMZ, forming N-methylthiourea, which is further metabolized by FMO to the reactive sulfenic and sulfinic acid (Mizutani et al, 2000). The sulfenic/sulfinic acid is most likely responsible for the hepatotoxicity (Mizutani et al, 2000), and presumably also OM toxicity, of MMZ.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that the bioactivation of MMZ is catalyzed sequentially by P450 and FMO, with P450 enzymes catalyzing the epoxidation of the C-4,5 double bond of MMZ, forming N-methylthiourea, which is further metabolized by FMO to the reactive sulfenic and sulfinic acid (Mizutani et al, 2000). The sulfenic/sulfinic acid is most likely responsible for the hepatotoxicity (Mizutani et al, 2000), and presumably also OM toxicity, of MMZ. However, the specific P450 enzymes responsible for MMZ metabolic activation have not been identified, and it is unclear whether target-tissue metabolic activation is essential for the OM toxicity.…”
Section: Introductionmentioning
confidence: 99%